Experimental investigation and simplified modeling of response of steel plates subjected to close-in blast loading from spherical liquid explosive charges. (March 2017) - Remennikov, Alex; Ngo, Tuan; Mohotti, Damith; Uy, Brian; Netherton, Michael
Highlights: Response of steel plates subjected to close-in detonation of liquid spherical charges is experimentally investigated. Effect of polyurea coating for blast mitigation of close-in blast loading has been studied. It is concluded that the side of the polyurea coating matters with a clear advantage for the polyurea coating being applied on the side opposite the explosive charge. The Blast Impact Impulse Model (BIIM) is presented for predicting the blast impulse for close-in detonation of a spherical explosive charge. The BIIM allows for rapid generation of the blast loads on the target due to close-in detonations by converting the specific blast impulse into the initial velocity boundary conditions for the steel plates. Abstract: Detonations of nitromethane spherical charges have been carried out to study close-in blast loading of steel plates and the effectiveness of several protective solutions. Three types of bare steel plates, namely mild steel, high-strength steel, and stainless steel were subjected to explosive blast loading. Steel plates of the same type with polyurea coating and composite covers were also subjected to localized blast loading. During an explosive field trial, the blast pressures and displacements of steel plates were measured. Additionally, loading of steel plates by the impinging detonation products was captured by high-speed video recordings. This experimental program has produced results which can be used to calibrate numerical models and to refine the simplified models for predicting blast loads and response of structural elements due to close-in detonations. The effectiveness of polyurea coating for enhancing blast protection of steel plated structures is discussed. The engineering-level model for predicting the blast impact impulse of the detonation gases from the charges in close proximity from the target is introduced and validated using the experimental results obtained during the course of the explosive trials.